ANALISIS PENGENDALIAN KUALITAS PRODUK BATU BATA PADA UMKM ANUGRAH JAYA DENGAN METODE PLAN, DO, CHECK, ACT DAN USULAN PERBAIKAN MENGGUNAKAN 5W+1H - Akbar Filayati Sasando; Ayudhyah Eka Apsari (Jurnal Cakrawala Ilmiah, 2024)
UMKM Anugrah Jaya is a company engaged in clay processing, with one of its products being bricks. In the period from January to December 2023, Anugrah Jaya MSMEs produced 184,335 units of bricks, but as many as 35,227 units (20%) were disabled. These types of defects include cracks, burns, and fractures. Of the total defects, cracks reached 2,139 units, burnt reached 29,019 units, and fractures reached 4,069 units. This study aims to identify the factors causing defects in brick products and provide improvement proposals. The method used is PDCA (Plan, Do, Check, Action), with tools such as Pareto Diagram, Fishbone Diagram, p-chart, and 5W+1H. The results showed that the factors causing disability are human, material, and method factors. Proposed improvements include regular inspections of production processes, purchasing materials from one supplier to maintain consistent raw material quality, as well as training on the use of moisture measuring devices and studies on more effective and efficient brick burning methods.